Land, agriculture and racial inequality in South West Africa (Historia, 2021)
Land, agriculture and racial inequality in South West Africa The settler colony of South West Africa under first German and then South African rule experienced broad land restructurings through which black Africans were displaced onto small 'native reserves' in the southern two-thirds of the colony, which became dependent upon the white-dominated livestock economy for trade and wages. A highly professional, competent, and autonomous agricultural extension service provided significant inputs to the white settler-farmers, and to a much lesser extent, to some of the communal areas. However, the assumption of direct South African control over the South West African bureaucracy in 1969 along with the creation of apartheid homelands displaced local agricultural specialists from both white and black rural areas. Most white farmers were not negatively affected as the administration of whites provided its own extension services; black farmers, however, only obtained minimal extension services (when contracted out by the respective homeland authority). Meanwhile, the veterinary department's construction of farm fences and a veterinary cordon fence ('red line') succeeded in keeping most of the country free of serious animal diseases for most of the 20 thcentury, reflecting the department's technical proficiency, but South Africa's politicization of the use of the cordon fence in the 1960s-1970s helped to assure the marginalization of northern communal area farmers while generating significant popular resentment.
Keywords: bureaucracy; land-holding; ethnically defined territories; political; racialist character; politicization of agricultural policy; agricultural bureaucracy